Information sources for obesity prevention policy research: a review of systematic reviews - Rosie Hanneke; Sabrina K. Young (Systematic Reviews, 2017)
Abstract Background Systematic identification of evidence in health policy can be time-consuming and challenging. This study examines three questions pertaining to systematic reviews on obesity prevention policy, in order to identify the most efficient search methods: (1) What percentage of the primary studies selected for inclusion in the reviews originated in scholarly as opposed to gray literature? (2) How much of the primary scholarly literature in this topic area is indexed in PubMed/MEDLINE? (3) Which databases index the greatest number of primary studies not indexed in PubMed, and are these databases searched consistently across systematic reviews? Methods We identified systematic reviews on obesity prevention policy and explored their search methods and citations. We determined the percentage of scholarly vs. gray literature cited, the most frequently cited journals, and whether each primary study was indexed in PubMed. We searched 21 databases for all primary study articles not indexed in PubMed to determine which database(s) indexed the highest number of these relevant articles. Results In total, 21 systematic reviews were identified. Ten of the 21 systematic reviews reported searching gray literature, and 12 reviews ultimately included gray literature in their analyses. Scholarly articles accounted for 577 of the 649 total primary study papers. Of these, 495 (76%) were indexed in PubMed. Google Scholar retrieved the highest number of the remaining 82 non-PubMed scholarly articles, followed by Scopus and EconLit. The Journal of the American Dietetic Association was the most-cited journal. Conclusions Researchers can maximize search efficiency by searching a small yet targeted selection of both scholarly and gray literature resources. A highly sensitive search of PubMed and those databases that index the greatest number of relevant articles not indexed in PubMed, namely multidisciplinary and economics databases, could save considerable time and effort. When combined with a gray literature search and additional search methods, including cited reference searching and consulting with experts, this approach could help maintain broad retrieval of relevant studies while improving search efficiency. Findings also have implications for designing specialized databases for public health research.